Optimasi Pemahaman Sastra: Penerapan Metode SQ3R Mahasiswa PBSI UIN Jakarta (2023) - Irhamna Irhamna; Hindun Hindun (LPPM Politeknik Pratama, 2024)
Reading has become a daily life for Indonesian Language and Literature Education students, as well as a necessity for everyone to improve the nation's information and literacy. This study measures the improvement of reading comprehension skills of literature among PBSI UIN Syarif Hidayatullah Jakarta 2023 students. The purpose is to review the application of the SQ3R method which involves the stages of Survey, Question, Read, Recite, and Review in the ability to read literary comprehension. The results of the study presented a significant improvement in the literary comprehension of PBSI students, with the success rate reaching 72.2%. Thus, this study implies that SQ3R is not only an efficient tool for understanding and appreciating literary works, but also plays a role in opening deeper insights. This research not only confirms the relevance of SQ3R in literature learning, but also provides a positive direction for the development of literary literacy learning strategies in the future